Analisis Faktor Sosiodemografi dan Pola Pemberian MP ASI terhadap Status Gizi Anak di Bawah Dua Tahun di Wilayah Pesisir Sumatera Utara: Analysis of Sociodemographic Factors and Complementary Feeding Patterns on Nutritional Status of Children under Two Years in Coastal Areas of North Sumatra - Sudaryati, Etti; Nurmaini, Nurmaini; Lubis, Zulhaida; Masthalina, Herta (Universitas Airlangga, 2025)
Background: Nutritional status is an indicator of growth, and the first two years of a child's life should be closely observed because it is a critical period for development. Failure to grow during this period will affect nutritional status. Many factors affect a child's nutritional status, including sociodemographic factors and patterns of complementary feeding of breast milk. Objectives: This study aimed to analyze the influence of sociodemographic factors and patterns of complementary feeding on the nutritional status of children under two years old in coastal areas of North Sumatra. Methods: This study used a cross-sectional approach involving 212 mother-child pairs aged 6-23 months in Pantai Labu District. Data collection involved structured questionnaires and interviews covering family characteristics, initial food introduction, breastfeeding status, and child age. Nutritional status was assessed through child length and weight measurements. Multiple logistic regression tests were conducted for multivariate analysis, and bivariate tests using chi-square. Results: The results showed that there was an influence of maternal knowledge (p-value=0.008; OR=2.678), maternal education (p-value=0.005; OR=2.807), and economic status (p-value=0.0001) on children's nutritional status. Most mothers (78.8%) provided timely complementary feeding and maintained hygienic practices (81.1%). Despite this, 15-20% of children exhibited poor nutritional status across weight-for-age, length-for-age, and weight-for-length indicators. Conclusions: Children's nutritional status in coastal areas is significantly influenced by sociodemographic factors. Integrated interventions targeting maternal capabilities and family economic conditions are crucial for improving child nutrition.